2019
DOI: 10.4103/nmj.nmj_1_19
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the academic performance and intelligence scores of asthmatic and nonasthmatic primary school pupils in Enugu State, Nigeria

Abstract: Background: Children with asthma (subjects), just as their non asthmatic colleagues, are expected to perform optimally academically and with a good intelligent score. A number of activities in children with asthma may be affected by asthmatic attacks including their education/academic performance. Report on academic performance and IQ of school children with asthma and comparisons with those without asthma (controls) within and outside Nigeria are scanty. Aims: This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Bronchial asthma is a leading cause of school absenteeism in school-age children worldwide including Nigeria. [45][46][47] Nduagubam, et al [45] in Enugu, southeast Nigeria, reported that children with bronchial asthma were more likely to be absent from school compared to their counterparts without asthma. Similar findings have been reported in parts of the developed countries.…”
Section: Childhood Bronchial Asthma and School Absenteeismmentioning
confidence: 99%
“…Bronchial asthma is a leading cause of school absenteeism in school-age children worldwide including Nigeria. [45][46][47] Nduagubam, et al [45] in Enugu, southeast Nigeria, reported that children with bronchial asthma were more likely to be absent from school compared to their counterparts without asthma. Similar findings have been reported in parts of the developed countries.…”
Section: Childhood Bronchial Asthma and School Absenteeismmentioning
confidence: 99%